Single-photon sources: Approaching the ideal through multiplexing - Meyer-Scott, Evan; Silberhorn, Christine; Migdall, Alan (Review of Scientific Instruments)
Keywords: Instrumentation

Improper Gaussian Signaling for the $K$-User MIMO Interference Channels With Hardware Impairments - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J (IEEE Transactions on Vehicular Technology)

Two-channel passive detection of cyclostationary signals - Horstmann, Stefanie; Ramírez, David; Schreier, Peter J (IEEE Transactions on Signal Processing)

Distillation of squeezing using an engineered pulsed parametric down-conversion source - Dirmeier, Thomas; Tiedau, Johannes; Khan, Imran; Ansari, Vahid; Müller, Christian R.; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (Optics Express)
Hybrid quantum information processing combines the advantages of discrete and continues variable protocols by realizing protocols consisting of photon counting and homodyne measurements. However, the mode structure of pulsed sources and the properties of the detection schemes often require the use of optical filters in order to combine both detection methods in a common experiment. This limits the efficiency and the overall achievable squeezing of the experiment. In our work, we use photon subtraction to implement the distillation of pulsed squeezed states originating from a genuinely spatially and temporally single-mode parametric down-conversion source in non-linear waveguides. Due to the distillation, we witness an improvement of 0.17 dB from an initial squeezing value of −1.648 ± 0.002 dB, while achieving a purity of 0.58, and confirm the non-Gaussianity of the distilled state via the higher-order cumulants. With this, we demonstrate the source’s suitability for scalable hybrid quantum network applications with pulsed quantum light.
Keywords: Atomic and Molecular Physics; and Optics

Die Wiedereinrichtung der Dombauhütten in Europa im 19. und 20. Jahrhundert - Silvestri, Marco; Seng, Eva- Maria (Le chantier cathédral en Europe. Diffusion et sauvegarde des savoirs, savoir-faire et matériaux du Moyen Âge à nos jours)

Einladung an Unbekannt und nicht-identitäre Frömmigkeit. Die Bedeutung von Kirchentagen für die Praxis evangelischer Spiritualität - Schroeter-Wittke, Harald (Handbuch Evangelische Spiritualität. Band 3: Praxis)

70 Jahre Kirchentag. Eine musikalische Zeitreise vom Bläserruf bis zum Abendsegen - Schroeter-Wittke, Harald; Fuhrmann, Christian; Greim, Ulrike; Groscurth, Reinhard (Deutscher Evangelischer Kirchentag Dortmund 2019. Dokumente)

Wie klingt, was du glaubst? Ouvertüre und Nachklang zur Leipziger Disputation 1519 - Schroeter-Wittke, Harald (Praktische Theologie)

Licht vom Licht – Tigran Hamasyans Luys i Luso. Zum 150. Geburtstag von Komitas - Schroeter-Wittke, Harald (Praktische Theologie)

Finding Gabriel. Zum 50. Geburtstag von Brad Mehldau - Schroeter-Wittke, Harald (Praktische Theologie)

Bibel als Klangraum - Bibliodrama und Musik - Schroeter-Wittke, Harald (Text-Raum)

David J. Burn, Grantley R. McDonald, Joseph Verheyden, Peter De Mey (ed.), Music and Theology in the European Reformations, Turnhout (Brepols) 2019 - Schroeter-Wittke, Harald (Francia recensio)

High cycle life all-solid-state fluoride ion battery with La 2 NiO 4+d high voltage cathode - Nowroozi, Mohammad Ali; Wissel, Kerstin; Donzelli, Manuel; Hosseinpourkahvaz, Niloofar; Plana-Ruiz, Sergi; Kolb, Ute; Schoch, Roland; Bauer, Matthias; Malik, Ali Muhammad; Rohrer, Jochen; Ivlev, Sergei; Kraus, Florian; et al. (Communications Materials)
Abstract Fluoride ion batteries (FIBs) are a recent alternative all-solid-state battery technology. However, the FIB systems proposed so far suffer from poor cycling performance. In this work, we report La 2 NiO 4.13 with a Ruddlesden-Popper type structure as an intercalation-based active cathode material in all solid-state FIB with excellent cycling performance. The critical charging conditions to maintain the conductivity of the cell were determined, which seems to be a major obstacle towards improving the cycling stability of FIBs. For optimized operating conditions, a cycle life of about 60 cycles and over 220 cycles for critical cut-off capacities of 50 mAh/g and 30 mAh/g, respectively, could be achieved, with average Coulombic efficiencies between 95 – 99%. Cycling of the cell is a result of fluorination/de-fluorination into and from the La 2 NiO 4+d cathode, and it is revealed that La 2 NiO 4.13 is a multivalent electrode material. Our findings suggest that La 2 NiO 4.13 is a promising high energy cathode for FIBs.
Keywords: Mechanics of Materials; General Materials Science

8. Sonntag nach Trinitatis (2.8.1010). Joh 9,1-7: Schaffe Licht in dunkler Nacht - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Zur Relationalität des Gestischen – über den Zusammenhang von Körpern, Kleidern und Bewegung - Haller, Melanie; de Smit, Peer; Darian (Hg.), Veronika (Out of Line. Perspektiven gestischer Forschung, Berlin: Neofelis.)

Intersystem Crossing and Triplet Dynamics in an Iron(II) N-Heterocyclic Carbene Photosensitizer - Zobel, J. Patrick; Bokareva, Olga S.; Zimmer, Peter; Wölper, Christoph; Bauer, Matthias; González, Leticia (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Revealing Hot and Long-Lived Metastable Spin States in the Photoinduced Switching of Solvated Metallogrid Complexes with Femtosecond Optical and X-ray Spectroscopies - Naumova, Maria A.; Kalinko, Aleksandr; Wong, Joanne W. L.; Abdellah, Mohamed; Geng, Huifang; Domenichini, Edoardo; Meng, Jie; Gutierrez, Sol Alvarez; Mante, Pierre-Adrien; Lin, Weihua; Zalden, Peter; Galler, Andreas; et al. (The Journal of Physical Chemistry Letters)
Keywords: General Materials Science; Physical and Theoretical Chemistry

Exploring the light-induced dynamics in solvated metallogrid complexes with femtosecond pulses across the electromagnetic spectrum - Naumova, Maria A.; Kalinko, Aleksandr; Wong, Joanne W. L.; Alvarez Gutierrez, Sol; Meng, Jie; Liang, Mingli; Abdellah, Mohamed; Geng, Huifang; Lin, Weihua; Kubicek, Katharina; Biednov, Mykola; Lima, Frederico; et al. (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Improving scenario-technique by a semi-automatized consistency assessment based on pattern recognition by artificial neural networks - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Proceedings of the DESIGN 2020 16th International Design Conference; 26. - 29. Okt. 2020)

Solidarität vs. Ressourcensouveränität? Die dritte Seerechtskonferenz als Herausforderung für die Süd-Süd-Beziehungen - Sackel, Johanna (Nord/Süd Perspektiven auf eine globale Konstellation)